Active effect of super-hydrophobicity on droplet nucleate boiling. (August 2020) - Zou, Lei; Wang, Hong; Zhu, Xun; Ding, Yudong; Liao, Qiang
Highlights: Bubble inside droplet on a hydrophobic surface can break up continually. Bubble generation inside droplet on a hydrophilic surface needs a waiting period. Hydrophobicity promotes the droplet to enter the nucleate boiling stage earlier. Super-hydrophobicity increases the heat transfer rate by 381.25%. ABSTRACT: It is well known that a surface with microstructures can be used to promote droplet nucleate boiling. However, the effect of the microstructure wettability on the droplet nucleate boiling is unknown. In this article, a test surface consists of two regions, one square region with microstructures is fabricated in the central area of the test surface, and another region keeps smooth. The droplets can maintain a similar shape before boiling so that the influence of droplet morphological changes on the boiling of the droplets is avoided. Surfaces with more hydrophilic and super-hydrophobic microstructures are called heterogeneous hydrophilic and heterogeneous hydrophobic surfaces, respectively. The result shows that the super-hydrophobic microstructure can promote the droplet to enter the nucleate boiling state at a lower superheat. The reason is that when the bubbles break up at the surface of the droplet, the super-hydrophobic substrate can attract part of the vapor to be trapped under the droplet. This part of the trapped bubble will continue to grow up and break up, leading the droplet entering the nucleate boiling state. Compared with the smooth hydrophilic surface, the heat transfer rate of the droplet on the heterogeneous hydrophobic surface can increase 381.25% for a superheat of 20 K. Graphical Abstract: Image, graphical abstract